JAPANESE ECONOMIC MIRACLE AND ITS CONSEQUENCES - Ubaydullaeva, Vasila; Bazarbayev, Diyarbek (Science technology&Digital finance, 2023)
This article analyzes the environment in such systems as the financial, domestic and foreign market, trade, light industry, which occurred in Japan after the Second World War, that is, in short, in relation to the economic changes that took place in the state and their consequences.